2011
DOI: 10.5951/jresematheduc.42.3.0237
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Development of Preschoolers' Mathematical Patterning

Abstract: The development of patterning strategies during the year prior to formal schooling was studied in 53 children from 2 similar preschools. One preschool implemented a 6-month intervention focusing on repeating and spatial patterns. An interview-based Early Mathematical Patterning Assessment (EMPA) was developed and administered pre- and postintervention, and again following the 1st year of formal schooling. The intervention group outperformed the comparison group across a wide range of patterning tasks at the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
0
37

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(149 citation statements)
references
References 38 publications
7
105
0
37
Order By: Relevance
“…It is noteworthy that not only was the patterning group not superior to the literacy group on mathematics, but there was also no correlation between the patterning scores of all 39 children and their KEYmath algebra scores. The theoretical arguments advanced by numerous educators (Baroody, 1993, Clements & Sarama, 2007a, 2007b, 2007cPapic, 2007, Papic et al, 2011Warren, Cooper, & Lamb, 2006 and others) have indicated that there should be a relation between patterning and (pre)algebra for young children. However, these theorists were speaking of simple alternating patterns, not complex patterns such as those used here and with first graders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that not only was the patterning group not superior to the literacy group on mathematics, but there was also no correlation between the patterning scores of all 39 children and their KEYmath algebra scores. The theoretical arguments advanced by numerous educators (Baroody, 1993, Clements & Sarama, 2007a, 2007b, 2007cPapic, 2007, Papic et al, 2011Warren, Cooper, & Lamb, 2006 and others) have indicated that there should be a relation between patterning and (pre)algebra for young children. However, these theorists were speaking of simple alternating patterns, not complex patterns such as those used here and with first graders.…”
Section: Discussionmentioning
confidence: 99%
“…However, the control children came from another school, which suggest an alternative explanation. A study of preschoolers by Papic, Mulligan, & Mitchelmore (2011) had the same limitation. There are substantial practical difficulties in assigning children to conditions randomly when they are enrolled in educational programs.…”
Section: Introductionmentioning
confidence: 99%
“…Papic, Mulligan, and Mitchelmore (2011) gave preschoolers 14 sessions of instruction on alternating patterns in more complex configurations than those usually taught, and also added instruction on spatial structure tasks. Twenty-seven children from one Australian preschool served as the experimental group; 26 from another constituted a control group.…”
Section: The Effect Of Instruction On Alternating Patternsmentioning
confidence: 99%
“…Some researchers have explored children's ability to identify the repeating unit of an alternating pattern (Clements & Sarama, 2011;Miller et al, 2015;Papic et al, 2011;Rittle-Johnson et al, 2013). Papic et al (2011) studied children from two private Australian preschools which enrolled pupils who were competent in English (but 80% came from non-English-speaking backgrounds).…”
Section: The Development Of Children's Understanding Of Patternsmentioning
confidence: 99%
See 1 more Smart Citation